KAJIAN PENDAHULUAN POTENSI PANAS BUMI TEMPERATUR RENDAH-SEDANG DI CEKUNGAN KUTAI: STUDI KASUS DAERAH SAMBOJA DAN DONDANG - Jamaluddin, Jamaluddin; Datu, Rosdiana Angel; Kaunang, Imanuel (PETROGAS: Journal of Energy and Technology, 2025)
This study presents a preliminary survey to evaluate the low–medium temperature geothermal potential in the Kutai Basin, particularly in the Samboja and Dondang areas. Field observations were conducted at three hot spring sites in Samboja and two sites in Dondang. Geochemical analysis indicates that the hot springs in Samboja exhibit pH values ranging from 6.5 to 7.6 (neutral to slightly alkaline) with electrical conductivity (EC) values between 1005 and 1184 µS/cm. In contrast, the hot springs in Dondang display relatively neutral pH values (7.0–7.5) and slightly higher EC values ranging from 1120 to 1295 µS/cm. These characteristics suggest that the geothermal system in both areas is controlled by the interaction of meteoric water with sedimentary rocks of the Balikpapan and Kampungbaru formations, which are widely exposed in the Samboja–Dondang region. The moderate to relatively high EC values reflect ongoing mineral dissolution processes of silicates and carbonates, with a possible contribution of fluids channeled through active fault fractures acting as migration pathways for geothermal fluids. Geologically, the occurrence of hot springs along the Kutai fault system and sedimentary lithologies indicates that the Samboja and Dondang areas host a promising low–medium temperature geothermal system associated with shallow hydrothermal circulation.